Dasavatharam : From myth to modernity - a critical analysis Raja Morgan Veerappan - Veerappan, Raja Morgan (2014)
The purpose of this thesis is to establish that the movie Dasavatharam is a modernisation of a traditional mythology through the medium of film. Stories and themes from Lord Vishnu’s incarnations have been identified as being used in films as well as in other forms of art such as dance drama and shadow play whereby the message and story line is not altered. The research in the thesis was to identify how the movie Dasavatharam adapted the plot, characters and theme of the mythology to suit the modern audience’s psyche. The findings of the research show that the movie has made Indian mythology relevant to the modern times by concentrating on a present-day problem focusing on the effects of a bio-chemical weapon that threatens the existence of mankind and mother earth. The movie presents the idea which is derived from the mythology that God takes on incarnations (in the movie, Govind races against time to destroy the bio-chemical weapon) to establish dharma or righteousness and destroy tyranny and injustice on earth. In modern times, humans need to look back at these mythological stories to provide them with hope to carry on when faced with turmoil. Lord Vishnu’s Dasavatharam as well as the movie Dasavatharam educates one that in times of trouble, faith and belief in oneself and a higher power will lead to triumph. The movie provides an insight for humans that everyone needs to find the spirit of Vishnu within themselves so that earth is protected, heritage is preserved and culture, patronized. By doing so, man can give value to his world and meaning to his life. The movie Dasavatharam works towards spreading the message that the world is a playground, a rangabhoomi and that life is like a game, a leela. The movies we enjoy today are at times original in nature but at other times, are actually borrowed from the combination of various sources, mythology being one of them.